Gloria Patri : the history and theology of the lesser doxology - Ayo, Nicholas (Notre Dame, Ind. : University of Notre Dame Press, 2007)
"The Gloria Patri has been prayed from the beginnings of Christianity. In this one-sentence prayer, time and eternity are combined in a compressed expression of doxology, praise of God. In this book, Father Ayo examines the riches in this prayer: the philological, historical, and theological origins of Christian prayer itself, and the profound spiritual implications of the Gloria Patri."--BOOK JACKET.
Pt. 1. Doxology : word and concept -- Doxology as mystery of God -- The philology and theology of glory -- The history of the Gloria Patri doxology -- Pt. 2. The trinity in time and eternity -- "Father, Son, and Holy Spirit" -- "As it was in the beginning" - the glory of eternity and time -- "Is now" - the fullness of time and the hidden glory -- "And will be forever, world without end" - the fullness of grace and the revealed glory -- "Amen"
Includes bibliographical references (p. 127-129).
Keywords: Gloria Patri; Doxology -- History and criticism